AutoCAD 2009 and AutoCAD LT 2009 : No Experience Required. - McFarland, Jon (Serious skills., 2008)
Learning AutoCAD, like learning any complex computer program, requires a significant commitment of time and attention and, to some extent, a tolerance for repetition. AutoCAD 2009 and AutoCAD LT 2009: No Experience Required is a simple, yet engaging tutorial that takes readers through an entire project, designing a simple cabin from start to finish, while helping them become familiar with AutoCAD tools and techniques. As you work your way through the book, you'll familiarize yourself with the AutoCAD interface and basic commands, develop efficient drawing strategies, learn how to work with Aut.